Professores em construção: um estudo sobre a docência inicial numa faculdade confessional do sul do Brasil - Silva Junior, Pedro Paulo da (Universidade do Vale do Rio dos Sinos, 2016)
This research aimed to understand the construction process of beginning professors in universities. Took as the locus Murialdo School, located in the city of Caxias do Sul, state of Rio Grande do Sul. It is an isolated IES confessional character. With a view to meet the investigative purpose, a qualitative research was developed by listening, through semi-structured interviews, seven teachers from different areas, with up to three years of experience in university teaching. This choice enabled best to set the scope of the study. For the interpretation of the data, the principles of content analysis were used. The main theoretical contributions were based on the Hubermann studies, Marcelo Garcia, Freire, Anastasiou, pepper, Cunha, Mayor Ruiz, Gaetta and Maceto, Isaia, Nóvoa, Shön, Tardif, Zabalza and Zeballos. With a view to achieving the objectives, some issues were central: what motivates professionals from different areas to get involved in university teaching? How do teachers build the knowledge necessary for this profession? What are challenges in the practice of teaching and learning? What do values give the knowledge of the university pedagogy field? What expectations do they have on institutional support in their work? Further expanding the study, we seek to also understand the key experiences that lived in the early years of teaching careers and what they meant for their daily practices. Interested to know also as training and institutional development strategies can be mobilized to strengthen teaching. The data showed the "reality check" by passing the beginner teachers, confirming previous research. They recognize that their knowledge is empirical, inspired by his former teachers and his career as a student. Realize, however, generational changes, which require them an effort to understand their students, their cultures and study conditions. Realize they need knowledge to help them succeed in their work and are committed to exchange of experiences and collaborative training as important alternatives to do so. However, there are few mentions of needs that go beyond the instrumental and pragmatic view of knowledge ordering. Perhaps, given their professional status of origin, there is no awareness of the complexity of teaching as a training space that goes beyond the dimension of expertise. The spaces of institutional training and policies accordingly, are required by teachers entering the top teaching. Still it was not explained more fully in this commitment, becoming the suggestion of the investment required for ongoing formation and located in the very IES, and incentives for post-graduation courses and strict sense. The fragility of the incipient training and institutional support in the academic environment slow down and affect the construction of professionalism, that are more an individual responsibility than in policies that support higher education in the country.
Keywords: Professor iniciante; Desenvolvimento profissional docente; Choque de realidade; Assessoramento pedagógico; Beginner teacher teaching professional; Development; Reality check; Educational counseling; ACCNPQ::Ciências Humanas::Educação